Autologous stem cell transplantation in adults with atypical teratoid rhabdoid tumor: a case report and review - Jackson Griffith-Linsley; William Robert Bell; Aaron Cohen-Gadol; Diane Donegan; Angela Richardson; Michael Robertson; Kevin Shiue; Kathryn Nevel (CNS Oncology, 2024)
Aim: Atypical teratoid rhabdoid tumor (ATRT) is a rare and highly aggressive primary CNS neoplasm, predominantly observed in children. The use of autologous stem cell transplantation (ASCT) in pediatric ATRT has shown promise; however, its utility in adult ATRT remains unclear. Patients & methods: This study presents the case of an adult patient with ATRT who is in remission after ASCT and reviews the literature on ASCT in adults with ATRT. Four cases of ATRT in adults who underwent ASCT were identified, with pertinent data summarized. Results: All five patients survived longer than the historical average survival rate, four of whom had no clinical or radiographic evidence of disease at the final follow-up. Conclusion: Based on limited data, there may be a role for ASCT in the treatment of adults with ATRT.